Carotid Intima-Media Thickness and Anti-Phospholipid Antibodies in Patients with Systemic Lupus Erythematosus - C. Rollino; C. Massara; L. Besso; C. Marcuccio; M. Manganaro; T. Bertero; B. Montaruli; G. Beltrame; M. Ferro; G. Quattrocchio; F. Elia; F. Quarello (European Journal of Inflammation, 2009)
An increase in mortality due to accelerated atherosclerosis has been reported in patients affected with Systemic Lupus Erythematosus (SLE). Anti-phospholipid antibodies (aPA) may play a pathogenetic role in the development of atherosclerosis. We measured carotid intima-media thickness (IMT), as a surrogate parameter of atherosclerosis, by B-mode ultrasound examination in 42 patients affected with SLE (11 men and 31 women) and in 42 healthy age- and sex-matched subjects. Lupus Anticoagulant (LA) (APTT sensitive, silica clotting time, DRVVT), Anti-cardiolipin antibodies (ACA) IgG and IgM, anti-β2glycoprotein 1 (anti-β2GP1) IgG and IgM and anti-prothrombin (anti-PT) IgG and IgM in ELISA (Orgentec Bouty) were also detected. IMT was 0.538±0.128 mm (0.310–0.866 mm) in SLE vs 0.473±0.084 mm in healthy subjects (-p 0.003–). IMT correlated with patients’ age (p<0.005) and with C Reactive Protein (CRP) (p<0.005), but not with years of disease, hypertension, number of anti-hypertensive drugs, total cholesterol, serum creatinine and proteinuria. Sixteen patients (38%) had aPL: 12 LA, 6 ACA IgG, 4 ACA IgM, 4 anti-β2GP1 IgG, 3 anti-β2GP1 IgM, 2 anti-PT IgG and 1 anti-PT IgM. IMT was not statistically correlated with aPA. Positive and negative aPA patients only differed as regards glomerular filtration rate (76 ml/min vs 113 ml/min - p<0.01–). Frequency of aPA positivity was 50% in Patients with IMT >0.600 mm and 33.3% in those with IMT <0.600 mm. If LA positivity was considered separately, it was 41.6% in patients with IMT >0.600 mm and 23.3% in patients with IMT <0.600 mm. Among the 5 patients with IMT >0.7 mm, 2 had LA positivity (40%) vs 10/37 (27%) of those with minor carotid thickness. In conclusion, IMT, a surrogate parameter of atherosclerosis, was correlated with Patients’ age and CRP and not with presence of aPA, even though, in the group of patients with greater IMT, there was a non-significant higher proportion of positivity for anti-phospholipid antibodies, in particular for Lupus Anticoagulant.